Practice of Phoenix dactylifera (Dates) among Residents in Kg. Dato’ Ahmad Razali, Dengkil, Selangor: A Preliminary Study - Nur Syazana Umar; Dzulkhairi Mohd Rani; Muhammad Shamsir Mohd Aris; Zairina A. Rahman (International Association of Computer Science and Information Technology (IACSIT) Press, 2024)
In Malaysia, the increasing demands on prophetic diet are shown through huge numbers of prophetic food products manufactured by Malay Muslim’s companies such as Hiraq Marketing, Saffron Integrated Marketing, Qaseh Gold, Naturalherbs and many more. The mushrooming of prophetic food products has shown an increased awareness among Muslim community in Malaysia in practicing Sunnah of Prophet Muhammad S.A.W. Despite the increasing demands of prophetic diet, there are few studies done in Malaysia to determine the actual practice among Muslim Malaysian communities. This preliminary study, which consisted of 40 adult residents in Kg. Dato’ Ahmad Razali , Sepang found that 35% of the respondents consumed dates only during Ramadhan or fasting month and this result showed that the level of practice of dates consumption was still low. Therefore, further large scale study needs to be done to promote the consumption of this prophetic food, not only among Muslims but non-Muslims as well. The acceptance of prophetic foods may lead to a healthier eating practice, thus improving one’s health status.